1986
DOI: 10.1901/jeab.1986.46-281
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Negative Stimulus Presentations on Observing‐response Rates

Abstract: Theories of observing differ in predicting whether or not a signal for absence of reinforcement (S-) is capable of reinforcing observing responses. Experiments in which S-was first removed from and then restored to the procedure have yielded mixed results. The present experiments suggest that failure to control for the direct effect of presenting S-may have been responsible. Pigeons and operant procedures were used. Experiment 1 showed that presentations of S-, even when not contingent on observing, can raise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
2

Year Published

1987
1987
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
0
6
0
2
Order By: Relevance
“…First, when access is restricted to only one of the two stimuli (Sϩ or SϪ), the effects are dramatically different. If observing is allowed to produce the discriminative stimulus only during the richer reinforcement component, observing is maintained at a high rate; but if observing is allowed to be effective only during the extinction component, the rate of observing declines to a low level (Allen & Lattal, 1989;Dinsmoor, Browne, & Lawrence, 1972;Mueller & Dinsmoor, 1986;Mulvaney, Dinsmoor, Jwaideh, & Hughes, 1974;Preston, 1985). Similar results are obtained even when Sϩ and SϪ signal different rates or magnitudes of intermittent reinforcement (Auge, 1973a(Auge, , 1974Jwaideh & Mulvaney, 1976).…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…First, when access is restricted to only one of the two stimuli (Sϩ or SϪ), the effects are dramatically different. If observing is allowed to produce the discriminative stimulus only during the richer reinforcement component, observing is maintained at a high rate; but if observing is allowed to be effective only during the extinction component, the rate of observing declines to a low level (Allen & Lattal, 1989;Dinsmoor, Browne, & Lawrence, 1972;Mueller & Dinsmoor, 1986;Mulvaney, Dinsmoor, Jwaideh, & Hughes, 1974;Preston, 1985). Similar results are obtained even when Sϩ and SϪ signal different rates or magnitudes of intermittent reinforcement (Auge, 1973a(Auge, , 1974Jwaideh & Mulvaney, 1976).…”
mentioning
confidence: 55%
“…The rates of observing in the Sϩ/SϪ condition relative to those in the Sϩ only, SϪ only, mixed-stimulus only, and standard multiple-schedule conditions replicate a variety of important findings in the observing literature. Consistent with a large body of evidence, primarily from studies using pigeons as subjects, observing occurred at a higher rate when it produced both Sϩ and SϪ or only Sϩ than when SϪ was the only outcome of observing (see Allen & Lattal, 1989;Auge, 1974;Bowe & Green, 1988;Dinsmoor et al, 1972;Jwaideh & Mulvaney, 1976;Mueller & Dinsmoor, 1986;Preston, 1985). In addition, when observing responses were unnecessary or failed to produce stimuli correlated with the prevailing schedules of reinforcement, the rate of observing decreased (see Auge, 1973b;Bowe & Green, 1988).…”
Section: Ratmentioning
confidence: 72%
“…Most investigators who have examined that issue have concluded that it is not (for review and discussion, see Dinsmoor, 1983). The strongest evidence for the contention that Sis reinforcing came from the work of Lieberman, but Mueller and Dinsmoor (1984) were able to reproduce Lieberman's results under circumstances that indicated that the original interpretation was not correct, and Mueller and Dinsmoor (1986) have offered an alternative interpretation of those results. In recent years, attention has turned to other forms of information.…”
mentioning
confidence: 99%
“…Previous experiments (Blanchard, 1975;Browne & Dinsmoor, 1974;Dinsmoor, Browne, & Lawrence, 1972;Mulvaney, Dinsmoor, Jwaideh, & Hughes, 1974) found that S -did not function as a reinforcer. One positive demonstration by Lieberman (1972) was criticized by Mueller and Dinsmoor (1986), who showed that if S-occurred response-independently in addition to response-dependent S+ presentation, pigeons' observing was as frequent as in the case where both S+ and S-were presented responsedependently. Although strong evidence has not yet been obtained, this should not necessarily rule out the information hypothesis of conditioned reinforcement.…”
Section: Discussionmentioning
confidence: 99%